(untitled) (Journal of actual problems of jurisprudence, 2018)
The issues about what Kazakhstani administrative justice should be in modern Kazakhstani legal science are still open. With that, it is gratifying to note that the research on the development of administrative justice issues is conducted in several alternative directions. At all stages of the reform of the state, were in dire issues that were aimed at improving the administrative legislation and, in general, administrative law. Key words: justice, law, public administration, administrative, rights.